The Laparoscopically Harvested Omental Free Flap: A Compelling Option for Craniofacial and Cranial Base Reconstruction - Costantino, Peter D.; Shamouelian, David; Tham, Tristan; Andrews, Robert; Dec, Wojciech (Journal of Neurological Surgery Part B: Skull Base, 2017)
Background Management of craniofacial and cranial base tumors is a challenge due to the anatomic intricacies associated with the calvarium, the pathological diversity of lesions that present, and the potential complications. Clinical outcomes in laparoscopically harvested omentum free flaps for cranial base and craniofacial reconstruction are presented in this paper, in the largest case series to date.Methods A retrospective single-center experience for over 10 years with laparoscopically harvested omentum flaps used to reconstruct craniofacial and cranial base defects.Results A total of 13 patients underwent craniofacial or cranial base reconstruction using laparoscopically harvested omentum free flaps. The mean patient age was 48 years. The anterior skull base represented the most common site of reconstruction. A total of 12 of the flaps survived (92%), with one flap failure due to infection. All patients demonstrated satisfactory aesthetic and functional outcomes. There were no perioperative or intra-abdominal complications.Conclusions The laparoscopically harvested omentum free flap is a safe and effective tool in the armamentarium of the reconstructive surgeon. It is the ideal option to treat complex, three-dimensional subcutaneous defects, such as those encountered in craniofacial and cranial base reconstruction. Its unique angiogenic and immunologic capacity makes it an excellent flap for the previously irradiated and/or infected wound bed.
Keywords: free flap; reconstruction; omentum free flap; craniofacial reconstruction; cranial base reconstruction; microvascular reconstruction